AUDIT OPERASIONAL ATAS PENJUALAN BAHAN BAKAR MINYAK (Studi Kasus Pada SPBU 24-316-156 PT. May Day Raksa Muara Kelingi) - Masri Ermawijaya; Endang Endang (Institut Rahmaniyah Sekayu, 2026)
This study aims to determine whether the implementation of the operational audit of fuel sales at Gas Station (SPBU) 24-316-156 PT. May Day Raksa Muara Kelingi conducted by PT Pertamina has been adequate. This research employed both qualitative and quantitative approaches. Data were collected through observation, interviews, and documentation. Data analysis was carried out by comparing fuel sales data in 2024 before and after the implementation of the operational audit. The results indicate that the operational audit of fuel sales at Gas Station 24-316-156 PT. May Day Raksa Muara Kelingi has been adequately implemented. The audit was conducted through the examination of documents, operational procedures, and the physical condition of the gas station facilities in accordance with the operational standards established by PT Pertamina. The audit serves to improve the effectiveness, efficiency, and compliance of the company's operational procedures. The analysis revealed that the highest average decline in fuel sales occurred in Solar fuel (13.14%), followed by Pertalite (12.29%), Pertamax Turbo (8.14%), Pertamax (7.86%), Pertamina Dex (6.79%), and Dexlite (5.00%). The decline was not directly caused by the implementation of the operational audit but was more influenced by changes in consumer demand, economic conditions, transportation activities, and business competition.